2004
DOI: 10.1097/01.asn.0000136300.72480.86
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane Receptor Mediates Renal Vasoconstriction and Contributes to Acute Renal Failure in Endotoxemic Mice

Abstract: Abstract. Sepsis is a major cause of acute renal failure (ARF) and death. Thromboxane A2 (TxA 2 ) may mediate decreases of renal blood flow (RBF) and/or GFR associated with LPSinduced sepsis. This study tested whether TxA 2 receptor blockade, with the use of TxA 2 receptor knockout (TP-KO) mice or a selective TP receptor antagonist (SQ29,548), would alleviate LPS-induced renal vasoconstriction and ARF. Under basal conditions, anesthetized TP-KO mice displayed a lower mean arterial pressure than wild-type (WT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 50 publications
3
53
0
Order By: Relevance
“…The constriction involves the preglomerular vasculature (20,21). Furthermore, we have demonstrated using both thromboxane (TxA 2 ) receptor knockout mice and a TxA 2 receptor antagonist that TxA 2 receptors mediate the increased RVR and contribute to the reduced GFR during endotoxemic shock (19). Other studies highlight the role of endothelin and the cytokine TNF-␣ in sepsis-induced ARF (22,23).…”
Section: T He Incidence Of Severe Sepsis Is Increasing In the Unitedmentioning
confidence: 93%
See 2 more Smart Citations
“…The constriction involves the preglomerular vasculature (20,21). Furthermore, we have demonstrated using both thromboxane (TxA 2 ) receptor knockout mice and a TxA 2 receptor antagonist that TxA 2 receptors mediate the increased RVR and contribute to the reduced GFR during endotoxemic shock (19). Other studies highlight the role of endothelin and the cytokine TNF-␣ in sepsis-induced ARF (22,23).…”
Section: T He Incidence Of Severe Sepsis Is Increasing In the Unitedmentioning
confidence: 93%
“…Although endotoxin injection and cecal ligation and puncture, an alternative sepsis model, vary by different cytokine kinetics, both models seem to induce ARF with common signaling pathways and similar sensitivity to therapeutic targets (32). We slightly adapted the initial experimental conditions by increasing the LPS dose to 8.5 mg/kg to mimic more closely septic shock in humans as described previously (19). For this reason, we focused on a relatively late phase of sepsis to simulate a short time-window of undiagnosed clinical sepsis during which one would determine whether drugs that are used routinely, such as NE, or more recently tested (NOS inhibition, AVP) in human septic shock would ameliorate LPSinduced reductions in GFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although selective COX-2 inhibitors have been shown to decrease proteinuria and retard progressive glomerular injury in experimental models of kidney disease, 22 the associated cardiovascular risks preclude the therapeutic use of COX-2 inhibitors in progressive renal injury. Thromboxane A 2 and thromboxane receptor activation mediate renal vasoconstriction and contribute to the pathogenesis of angiotensin-IIdependent hypertension, 23 progression of diabetic nephropathy, 24 -27 and renal failure in endotoxemic mice 28 or rats with 5/6 nephrectomy. 29 Older studies suggested that thromboxane synthase inhibitors or receptor antagonists were efficacious in streptozotocin-induced renal damage, 30 lupus nephritis, [31][32][33] cyclosporine nephrotoxicity, 34 -36 remnant kidney, 37 and renal allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, basal levels of TxA 2 contribute little to tubuloglomerular feedback-induced renal vasoconstriction in normotensive rats (7). Furthermore, basal RBF and RVR are in the normal range in TP receptor null mice (5).…”
mentioning
confidence: 99%